The dilemma of architectural conservation policy and practice versus sustainable tourism: The case of the Great Shangqinggong Temple in Jiangxi Province, People’s Republic of China - Liu, Xin (Thai Journal of East Asian Studies, 2024)
This qualitative research addresses the dilemma of architectural conservation policy and practice versus sustainable tourism goals through a case study of the Great Shangqinggong Temple. The goal is to determine how local agencies manage heritage places such as archaeological ruins to fulfill the demands of sustainable tourism, retaining authenticity in architectural conservation policy while presenting heritage to attract tourist consumption. Whether to commercialize an archaeological site for tourist entertainment or focus on interpretation and education is a question central to site management. Data was gathered by a literature review of Chinese Taoist history and participant observation of the Great Shangqinggong Temple compared to the Xiandu Female Taoist Temple, Magu Mountain. The result was that an architectural conservation policy, practice, and sustainable tourism requires authenticity to maintain equilibrium.